2022
DOI: 10.3847/1538-4357/ac89ec
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid Measurements at Millimeter Wavelengths with the South Pole Telescope

Abstract: We present the first measurements of asteroids in millimeter wavelength data from the South Pole Telescope (SPT), which is used primarily to study the cosmic microwave background (CMB). We analyze maps of two ∼270 deg2 sky regions near the ecliptic plane, each observed with the SPTpol camera ∼100 times over 1 month. We subtract the mean of all maps of a given field, removing static sky signal, and then average the mean-subtracted maps at known asteroid locations. We detect three asteroids—(324) Bamberga, (13) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recently, the South Pole Telescope (SPT; Carlstrom et al 2011) team reported flux measurements for a trio of main-belt asteroids (Chichura et al 2022). For two of the three asteroids they detected, the flux measurements were consistent with predictions derived from WISE observations of unitary emissivity; for the third, the measured emissivity was ò = 0.64 ± 0.11.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, the South Pole Telescope (SPT; Carlstrom et al 2011) team reported flux measurements for a trio of main-belt asteroids (Chichura et al 2022). For two of the three asteroids they detected, the flux measurements were consistent with predictions derived from WISE observations of unitary emissivity; for the third, the measured emissivity was ò = 0.64 ± 0.11.…”
Section: Introductionmentioning
confidence: 54%
“…We directly compare our observations of (324) Bamberga, (13) Egeria, and (22) Kalliope to those made by SPT in Chichura et al (2022), specifically to the effective emissivity listed in Table 1 of that paper. We present the comparison in Table 2.…”
Section: Sptmentioning
confidence: 99%
“…In the case of amateur astronomers, they can perform calculations and re-analyze the orbit of an asteroid or comet to inspect whether or not a close encounter or even a collision is possible. Furthermore, we can understand in depth whether these small objects are dangerous or not from their ephemeris that can be obtained from observations (Chichura et al, 2022). This article will explain step-by-step how to determine the orbit of an asteroid and the potential danger it has, with the object as the case is asteroid Apophis.…”
Section: Introductionmentioning
confidence: 99%